Pemberdayaan Masyarakat melalui Urban Farming di Rusun Marunda Jakarta Utara - Nisa Maidah Rahmawati; Joko Winarno; Agung Wibowo (Universitas Sebelas Maret, 2020)
Agricultural land in the city has decreased because of land-use transition. They people who lived in worst area or state-owned land has to move in the flats was provided by government. Public space in front of Marunda flats used for urban farming and man’s skill in agriculture who participated empowerment activity is not still enough, flats’ irrigation has defiance and group working isn’t fair so yet, it makes the society chooses to do agriculture activities by themselves. The purpose of this research is: to know external and internal factors are obstruct empowerment activities arranged in Marunda flats, to know empowerment activities in Marunda flats, and also to give recommendation about empowerment activities according to condition in Marunda flats. This research used purposive sampling in Marunda flats Jakarta Utara. Informants are selected by snowball sampling technique and data validity obtained by data source triangulation method. According to this research there are some external and internal factors which obstruct empowerment activities in Marunda flats. Marunda flats is society’s flats relocation in Jakarta consists of 4 cluster (cluster A,B, C and D) external factor obstruction are natural resources, environments, dynamics group, networking, human resources, policy, facilities and infrastructure. Internal factors obstruction are skill, non-formal education, and income. There some activities to fulfill empowerment implementation process held in Marunda flats are extension, training, controlling and evaluation. Design of activity according to situation of Marunda flats which are strengthening community organizations, optimizing the role of companions, and persuasive communication.